Penguatan Kemampuan Konseptual Anak Usia Dini melalui Pendekatan Pembelajaran Deep Learning di PAUD Al-Fathanah - Rahmat, Mamat; Rohmatin, Alfa; Siti Sarah Nurfadilah; Evi Mulyati; Siti Rohimah; Cep Wawan; Latipah Latipah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the implementation of a deep learning approach in developing conceptual understanding among early childhood learners at PAUD Al-Fathanah. A descriptive qualitative method was employed through observation, interviews, and documentation involving 15 children and one classroom teacher. The findings indicate that deep learning effectively supports children’s conceptual development by engaging them in meaningful exploration, purposeful play, and real-life learning experiences. Children were able not only to recall information but also to connect new ideas with everyday situations. Additionally, the learning environment promoted a sense of comfort and enjoyment, as children displayed higher levels of enthusiasm and active participation. The child-friendly atmosphere and well-designed play-based activities contributed to joyful and meaningful learning experiences. This study concludes that deep learning is a promising approach to strengthening conceptual understanding, enhancing learning comfort, and increasing children’s motivation to learn. These findings highlight the importance of designing child-centered, contextual, and reflective learning experiences in early childhood education.